Seed coating application of endophytic and rhizosphere bacteria for germination enhancement and seedling growth promotion in soybeans - Kangsopa, J.; Atnaseo, C. (International Journal of Agricultural Technology, 2022)
Stenotrophomonas sp. and Bacillus sp. isolated from rhizosphere and seed of kale, respectively, were found to have IAA producing activity but lack ability to solubilize phosphate. When used as an active ingratient for soybean seed coating, it was apparent that under laboratory environment, soybean seeds coated with 1x107 CFU/mL Stenotrophomonas spp. resulted in higher rate of germination and higher speed of germination compared to uncoated seeds. However, under greenhouse condition, coating soybean seed with bacteria did not show differences in germination and speed of germination. In term of growth, seed coated with 1x107 CFU/mL Bacillus sp. resulted in higher fresh and dry weight of seedlings when examined in laboratory conditions and better fresh and dry weight of shoot in greenhouse conditions although it did not enhance seedling or shoot length. Therefore, application of Bacillus sp. at the concentration of 1x107 CFU/mL as an active ingradient in soybean seed coating was an appropriate method for enhancing soybean production